ANALISIS YURIDIS BATALNYA PERJANJIAN PRA- NIKAH DALAM PERKAWINAN CAMPURAN - Ayu Natashasia Sembiring; Agus Kristianto Sinaga; Satria Braja Hariandja (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Mixed marriages according to Law Number 1 of 1974 concerning marriage are marriages between Indonesian citizens and foreign nationals (Article 57). Because of different nationalities, the laws applied to them are also different. Marriage Law does not expressly regulate the legal consequences arising from Mixed marriages. According to the Marriage Law of citizenship which is obtained as a marriage result, marital disturbances determine the applicable law, about public law and civil law.This research is a normative legal research that is prescriptive with a legislative approach and a conceptual approach. The sources and types of legal materials used are primary legal materials that are supported by secondary legal materials. Pre-Marriage Agreement Research Results is not implemented in good faith by each party that makes a prenuptial agreement so that it is null and void.